Evaluasi Kinerja Teknologi Informasi Menggunakan Cobit 4.1 (Studi Kasus : PT. Al-Yaubi Tour & Travel) - Solehudin Al Ayyubi Ayyubi (Universitas Mercu Buana Yogyakarta, 2023)
Information Technology is almost implemented in all companies, PT. Al-Yaubi is not one of the companies that have implemented a web-based information system. PT. Al-Yaubi is a Tour & Travel company. In carrying out a business process, there are factors that must be considered by the company, including the use of technology, maintenance, monitoring and regulations made by the company to support business processes. For the problem in the case study, the researcher will use the Monitor and Evaluate domain using the COBIT 4.1 framework which aims to measure how mature the company's information technology is. The research objectives are based on the process of maintenance, handling and compliance with regulations. The results of this study aim to reach the company's maturity level and provide input to the company for better, efficient and effective IT applications.